1999
DOI: 10.1055/s-1999-13957
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Natural Ginseng Glycosides and Semisynthetic Analogues

Abstract: The cytotoxicity of natural glycosides from Ginseng, semisynthetic analogues and related triterpenes of the dammarane series, isolated from the leaves of the Far-East species of the genus Betula was studied in order to elucidate structure-activity relationships. Some of the compounds studied were active against the human lung carcinoma GLC4 and adenocarcinoma COLO 320 cell lines. The natural glycosides displayed the lowest cytotoxicity. The triterpenes of the dammarane series used as starting aglycones for sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 7 publications
1
32
0
2
Order By: Relevance
“…It has been reported that ginsenosides are metabolized by intestinal bacterial and the intestinal bacterial metabolites were responsible for the main pharmacological activities of ginseng (12)(13)(14). However, the intestinal bacteria are liable to be influenced by a human's makeup and his dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ginsenosides are metabolized by intestinal bacterial and the intestinal bacterial metabolites were responsible for the main pharmacological activities of ginseng (12)(13)(14). However, the intestinal bacteria are liable to be influenced by a human's makeup and his dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…We prepared semisynthetic glycosides of 20S-protopanaxadiol and their analogs by chemical transformation of betulafolientriol, a component of the extract of birch (Betula) leaves [11][12][13][14]. Then, they were tested biologically [15][16][17][18][19][20]. Unfortunately, compounds that could be used as starting materials for synthesizing 20S-protopanaxatriol glycosides were not found among the many dammarane triterpenoids isolated from Betula leaves [21].…”
mentioning
confidence: 99%
“…Ginseng glycosides are transformed by intestinal microflora in the gastro-intestinal tract into compounds with new biological properties. In the last few years, the properties and mechanism of action of one of the main metabolites of ginseng glycosides, 20S-protopanaxadiol 20-O-β-D-glucopyranoside (1) (compound K), have been studied more frequently [1][2][3][4][5][6][7][8][9][10][11][12][13]. Glucoside 1 inhibits the growth of tumor cells and induces their apoptosis [3,9,10], decreases the toxicity of antitumor preparations [4], possesses antimetastatic and immunomodulating activity [2,11], and exhibits antiallergic [12] and anti-inflammatory [13] properties.…”
mentioning
confidence: 99%